Performance Evaluation Criterion at Equal Pumping Power for Enhanced Performance Heat Transfer Surfaces. (10th June 2013) - Karwa, Rajendra; Sharma, Chandresh; Karwa, Nitin
Abstract : The existing equations for the thermal performance evaluation, at equal pumping power for the artificially roughened and smooth surfaced multitube and rectangular duct heat exchangers, have been critically reviewed because the literature survey indicates that a large number of researchers have not interpreted these equations correctly. Three of the most widely used equations have been restated with clearly defined constraints and conditions for their application. Two new equations have been developed for the design constraints not covered earlier.